2014
DOI: 10.1007/s00441-014-2073-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the heparin-binding growth factor midkine and its receptor, Ptprz1, in adult rat pituitary

Abstract: Midkine (MK) belongs to a family of secreted heparin-binding growth factors and is highly expressed in various tissues during development. MK has multiple functions, such as regulation of cell proliferation, migration, survival and differentiation. We recently reported that MK mRNA is strongly expressed in the developing rat pituitary gland. In the adult pituitary, however, expression of MK and its receptor and the characteristics of the cells that produce them, have not been determined. Therefore, in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…1c, g). We previously detected MK mRNA in FS cells [8]. In the present study, MK mRNA was detected in some RALDH1-immunopositive cells (Fig.…”
Section: In Situ Hybridization and Immunohistochemistrysupporting
confidence: 76%
See 3 more Smart Citations
“…1c, g). We previously detected MK mRNA in FS cells [8]. In the present study, MK mRNA was detected in some RALDH1-immunopositive cells (Fig.…”
Section: In Situ Hybridization and Immunohistochemistrysupporting
confidence: 76%
“…In a previous study, we reported that the MK receptor Ptprz1 was expressed in somatotrophs and corticotrophs in rat anterior pituitary gland [8]. We hypothesized that MK produced in FS cells acts locally on these hormone-producing cells via PTPRZ1 in the anterior pituitary.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…GH and midkine (MDK) relation should be investigated Midkine (MK), a heparin-binding growth factor that seems to play an important role in arteriogenesis by mediating NO synthases and increasing the bioavailability of VEGFA [186], has also been related with GH, as expression of MK and its receptors have been detected in somatotrophs of both embryonic and adult rats, favoring the development of pituitary gland [187] and acting as a regulator of its function in the adult. MK seems to be secreted by follicle stimulating cells, controlling GH production from GH cells in a paracrine way via protein tyrosine phosphatase receptor-type Z (Ptprz1) [188]. MK is involved in the process of mechanosensing to SSF, as its receptor has an identical structure of sensors for laminar shear stress and induces a very similar signal cascades [189].…”
Section: Gh and Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%